The Role of Career Self-Efficacy on the Effect of Parental Career Behaviors on Career Exploration: A Study on School of Tourism and Hotel Management’ Students - Kanten, Selahattin; Kanten, Pelin; Yeşiltaş, Murat (European Journal of Multidisciplinary Studies, 2016)
This study aims to investigate the impact of parental career behaviors on undergraduate student’s career exploration and the mediating role of career self-efficacy. In the literature it is suggested that some social and individual factors facilitate students’ career exploration. Therefore, parental career behaviors and career self-efficacy is considered as predictors of student’s career exploration attitudes within the scope of the study. In this respect, data which are collected from 405 undergraduate students having an education on tourism and hotel management field by the survey method are analyzed by using the structural equation modeling. The results of the study indicate that parental career behaviors which are addressed support; interference and lack of engagement have a significant effect on student’s career exploration behaviors such as intended-systematic exploration, environment exploration and self-exploration. In addition, it has been found that one of the dimensions of parental career behaviors addressed as a lack of engagement has a significant effect on career self-efficacy levels of students. However, research results indicate that student’s career self-efficacy has a significant effect on only the self-exploration dimension. On the other hand, career self-efficacy has a partial mediating role between lack of engagement attitudes of parents and career exploration behaviors of students.